Pronounced resting bradycardia in male elite runners is associated with high heart rate variability - Jensen-Urstad, K.; Saltin, B.; Ericson, M.; Storck, N.; Jensen-Urstad, M. (Scandinavian Journal of Medicine & Science in Sports, 1997)
Forty-eight hour Holter monitoring was undertaken of 16 male elite middle- and long-distance runners, age 25 +/- 3 years, with peak oxygen uptake 4.83 +/- 0.43 1 O2/min or 73.0 +/- 3.9 ml O2/kg/min. The athletes had pronounced bradycardia during the night-time, with heart rate calculated from four RR intervals < 30 beats/min in five runners. Twelve of 16 runners had RR intervals > 2 s. Of those, 10 runners had sinus pauses exceeding 2 s, the longest being 3.06 s. Three runners had AV block II, two with Mobitz type 1, and one with both Mobitz type 1 and 2. Autonomic function was estimated by time domain and power spectral analysis of heart rate variability. The runners were compared with a control group of 13 sedentary or moderately active subjects. The runners had a mean of 14 b.p.m. lower heart rate at night than the controls. The runners had higher heart rate variability in all spectral bands. In the time domain pNN50 and rMSSD, which are considered to reflect strongly vagal tone, were markedly higher in the runners than the controls. The findings suggest that an increased parasympathetic tone might at least partly explain the pronounced resting sinus bradycardias found in endurance-trained runners.